PERAN KERABAT DALAM PENDIDIKAN AKHLAK ANAK - Iin Meriza (SCAD Independent, 2014)
Conditions acehnese matrifokalti and bustle that mothers who work for a living give a new color to the patterns moral education of children in the family. The existence of a close relative in the family increase the quantity in a family of educators. In addition, also, where relatives can also replace the parents who entrust their children to. In contrast to guard children generally, in nature, relatives were able to give love to children.